Collocation Competence : A Case Study of Undergraduate Students - Siriporn Tungyai; Singkham Rakpa (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
This study aims to investigate the collocations competence by Thai university students, classify the type of grammatical collocation and lexical collocation that is the most problematic and explore the strategy uses in facing difficulties of collocation. The participants of the study were 34 fourth-year English major students of the University of Phayao. The research instruments used to investigate the participants' competence of English collocation were 30 lexical collocation and 30 grammatical collocation bases on Benson et al. (2010)'s strategy and explore the strategy uses in facing difficulties of collocation by semi-structured interview. The results revealed that the competence in English collocations of the participants was quite low (44.46%). The findings showed that the most problematic lexical group was found in Verb + Adverb (32.35%), followed by Adjective + Noun and Verb + Noun are the same score (47.35%). For grammatical collocation, the most problematic was found in Adjective + Preposition (41.76%). This was followed by Preposition + Noun (46.18%) and Noun + Preposition (51.76%), respectively. The results also pointed out that the word retrieval strategy was most frequently used (58.33%), followed by the approximate translation strategy (41.67%) respectively.